Comparison of Sukuk and Bonds in Capital Market Activities: Indonesia - Fauzan, Dimas Fauzan Azhim; Hilmi Al Hafidz; Difa Zahwa Silviana (FEBI UIN Sunan Kalijaga Yogyakarta, 2022)
Formally, the capital market is a market for various tradable long-term financial instruments (or securities). The emergence of the Islamic stock market is very important to reduce financial scandals in international capital markets such as sukuk and bonds. The method applied in carrying out this online service is information on Islamic capital market activities. The result of this study is that the difference between interest rates and bonds lies in the use of compensation and profit sharing as a substitute for interest. Sukuk has the principle of shared ownership of the underlying (necessary) which gets returns in the form of profit sharing, fees, ujrah, and margins. Meanwhile, the principle of bonds has the principle of debt inquiries from accounts payable between debt issuers (bonds) and investors who get returns from interest for a certain period and a predetermined time. Keywords: Capital Market, Sukuk, Bonds.